THE ASSOCIATION BETWEEN HB LEVELS AND PLACENTA PREVIA IN GRAVIDA PATIENTS - Herlin Ajeng Nurrahma; Yulice Soraya Nur Intan; Andreanyta Meliala; Paramita Narwidina (Jurnal Keperawatan Respati Yogyakarta, 2022)
A placenta previa develops in the lower part of the uterus, covering the internal uterine ostium entirely or partially. The risk of maternal and infant mortality and morbidity rises as the placenta's inadequate vascularization expands to cover the entire birth canal. Hemoglobin (Hb) level is a biochemical indicator to determine the nutritional status of pregnant women, and reduced blood supply to the placenta can be caused by a lack of Hb levels in pregnant women. The purpose of this study was to determine the association between Hb level in gravida patients and the incidence of placenta previa at Sultan Agung Islamic Hospital, Semarang. This research was an observational analytic study with a cross-sectional design, which was conducted on 97 respondents who met the inclusion and exclusion criteria. The data was taken from the patient's medical record document from January 2017 - January 2018 at Sultan Agung Islamic Hospital. Analysis of the research data using the Chi-Square test. The findings revealed a significant correlation between Hb level and placenta previa incidence, low Hb levels (<11 g/dl) could significantly increase the risk of placenta previa in gravida patients.